Chemoradiotherapy‐induced increase in Th17 cell frequency in cervical cancer patients is associated with therapy resistance and early relapse. Issue 12 (13th September 2021) - Theobald, Laura; Stroeder, Russalina; Melchior, Patrick; Iordache, Ioan Iulian; Tänzer, Tanja; Port, Meike; Glombitza, Birgit; Marx, Stefanie; Schub, David; Herr, Christian; Hart, Martin; Ludwig, Nicole; et al.
Abstract : Cervical cancer therapy is still a major clinical challenge, as patients substantially differ in their response to standard treatments, including chemoradiotherapy (CRT). During cervical carcinogenesis, T‐helper (Th)‐17 cells accumulate in the peripheral blood and tumor tissues of cancer patients and are associated with poor prognosis. In this prospective study, we find increased Th17 frequencies in the blood of patients after chemoradiotherapy and a post‐therapeutic ratio of Th17/CD4 + T cells > 8% was associated with early recurrence. Furthermore, Th17 cells promote resistance of cervical cancer cells toward CRT, which was dependent on the AKT signaling pathway. Consistently, patients with high Th17 frequencies in pretherapeutic biopsies exhibit lower response to primary CRT. This work reveals a key role of Th17 cells in CRT resistance and elevated Th17 frequencies in the blood after CRT correspond with early recurrence. Our results may help to explain individual treatment responses of cervical cancer patients and suggest evaluation of Th17 cells as a novel predictive biomarker for chemoradiotherapy responses and as a potential target for immunotherapy in cervical cancer. Abstract : This study demonstrates that chemoradiotherapy‐treated patients with cervical cancer have increased frequencies of Th17 cells. Th17 frequency was associated with early cancer relapse. Additionally, high pretherapeutic Th17 amounts in situ were correlated to a failed response to chemoradiotherapy. Our work suggests that the evaluation of Th17 cells could serve as a novel predictive biomarker for chemoradiotherapy responses and a potential target for immunotherapy in patients with cervical cancers.